2016
DOI: 10.1002/nvsm.1571
|View full text |Cite
|
Sign up to set email alerts
|

How libraries can enhance customer service by implementing a customer value mindset

Abstract: Libraries have a rich tradition of solid customer service. Good service today, however, is often not good enough. Libraries can improve the customer experience by understanding what it means to truly deliver outstanding value. Implementing customer-centric marketing and the latest technology can increase the perceived value of library usage before, during, and after service delivery. The evolving library experience framework explains how library administrators can prepare for current challenges and future chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Freeze et al [19] indicated that a user satisfaction test should be undertaken to measure the success of the interaction between users and the information system. Weinstein and McFarlane [51] mentioned that for customers' needs to be met, service providers must go the extra mile and deliver more than just enough to meet the customers' basic needs. Some participants are concerned about their value for money.…”
Section: Discussionmentioning
confidence: 99%
“…Freeze et al [19] indicated that a user satisfaction test should be undertaken to measure the success of the interaction between users and the information system. Weinstein and McFarlane [51] mentioned that for customers' needs to be met, service providers must go the extra mile and deliver more than just enough to meet the customers' basic needs. Some participants are concerned about their value for money.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the last ten years, academic library service providers have progressively documented the implications of evaluating their library services. [2][3][4][5][6][7][8][9][10][11][12][13] . Nevertheless, measuring library quality based solely on collections of learning resources is obsolete 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the paper itself does not present a full picture of the model in a manner that would enable the practicing manager to readily implement; more details are needed. Weinstein and McFarlane's (2016) conceptual work identified and recommended ways in which libraries can enhance customer service by implementing and maintaining a customer value mind-set. Like Grieves and Halpin (2014) they highlight the importance of cultural change.…”
Section: Statementioning
confidence: 99%
“…Weinstein and McFarlane's (2016) roadmap, while value-adding and based on best practices and trends, would need to be translated into a program, with practical initiatives for implementation (a limitation also observed in Grieves' and Halpin's (2014) paper. Additionally, Weinstein and McFarlane's (2016) study was based primarily on North American and European libraries and the paper itself recommends "an increased global perspective should consider Asian and Latin American libraries, knowledge-disseminating enterprises, and nonprofit organizations" (Weinstein and McFarlane, 2016, p. 6); even within this recommendation, Caribbean libraries were not mentioned. This points to the need for Caribbean models in use, with practical initiatives for implementation and evidence of its effectiveness, through for example, a survey; this paper seeks to achieve this, albeit incrementally.…”
Section: Statementioning
confidence: 99%
See 1 more Smart Citation